Barriers of exclusive breastfeeding among mothers attending primary health-care centers in Jazan, Saudi Arabia - Gassem Gohal; Mai Mustafa; Ali A. A. Al-Makramani; Amani A. Ahmed; Sarah M. Salih; Amani O. Abdelmola; Mohamed W. Elsharief (Journal of Family Medicine and Primary Care, 2023)
Background: Exclusive breastfeeding (EBF) describes infants who were only breastfed for 6 months. Many Saudi mothers have suboptimal breastfeeding practices. Therefore, this study aims to assess breastfeeding knowledge and determine barriers to EBF among mothers attending primary health care centers in Jazan City. Methods: A descriptive cross-sectional study was done that included all mothers attending the PHC centers. Data were collected through a self-administered questionnaire. Results: Most study participants understand breastfeeding’s health benefits for babies and mothers, but most believe that synthetic milk is the best alternative for working mothers to feed their babies. A percentage of 66.7 of mothers practiced breastfeeding during the first 6 months of the child’s life. EBF shows a significant relationship with knowledge and barriers. Sixty percent of mothers have never had any information about breastfeeding; the primary source was from their mothers and only 31.4% from hospital staff. Most respondents disagreed with statements of barriers to EBF, which elicits an unexpected response. Conclusions: Most participants have good knowledge concerning breastfeeding benefits for both mother and infant and disagreed on the mentioned barriers for EBF that include lack of breastmilk, deficiency of information, and working conditions.